Automotive Design Sketching in Teams: A Systematic Review - Abdul Rahim, Mohamad Fairuz; Nik Ahmad Ariff, Nik Shahman; Mohammad Yusof, Nur Athirah Diyana; Badke-Schaub, Petra (Journal of Visual Art and Design, 2024)
Automotive design sketching is crucial in the creative process, especially during conceptual design, as it facilitates shared understanding among design teams. Despite its significance, there need to be more comprehensive review papers addressing automotive design sketching in team settings. This systematic review aims to bridge this gap by identifying trends and evidence related to automotive design sketching within team settings. Employing the ROSES review flow diagram, five electronic databases – Scopus, Web of Science, Science Direct, SAGE, and Google Scholar – were utilized to search for relevant literature. Among the 902 non-duplicated articles initially screened, 17 studies from the past decade (2013-2023) underwent a thorough review and were integrated into the analysis. The findings emphasize the importance of team sketching, highlighting collaboration, communication, and creativity as essential values for enhancing shared understanding and design outcomes within teams. Significantly, the review uncovered a shortage of articles in recent years that encompass all three elements within a single study. This paper highlights the critical role of sketching in team-based automotive design and advocates for further research to investigate collaboration, communication, and creativity comprehensively. This knowledge is valuable for automotive designers, teams, and the industry, emphasizing the need for holistic approaches to optimize design processes and foster innovation.